2008
DOI: 10.3762/bjoc.4.34
|View full text |Cite
|
Sign up to set email alerts
|

End game strategies towards the total synthesis of vibsanin E, 3-hydroxyvibsanin E, furanovibsanin A, and 3-O-methylfuranovibsanin A

Abstract: End game synthetic strategy studies towards the total synthesis of the vibsanin type diterpenes, vibsanin E, 3-hydroxyvibsanin E, furanovibsanin A, and 3-O-methylfuranovibsanin A are discussed, with focus on construction of the side chain and peripheral functionality associated with this group of natural products is the current focus of this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The overall conversion was represented in several simplified schemes showing the starting alcohol moiety (114) giving the eliminated enone function (i.e. 115) and the fragmented dialkylamine (116). [78,79] Furthermore, it was reported that catalytic hydrogenation of GB13 The Future of Retrosynthesis (113) in the presence of acid reconstituted himgaline (112), both installing the last nitrogen-containing ring (via an aza-Michael addition) giving oxohimgaline (not shown), and hydrogenating the resulting ketone to an alcohol (i.e.…”
Section: Chemical Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall conversion was represented in several simplified schemes showing the starting alcohol moiety (114) giving the eliminated enone function (i.e. 115) and the fragmented dialkylamine (116). [78,79] Furthermore, it was reported that catalytic hydrogenation of GB13 The Future of Retrosynthesis (113) in the presence of acid reconstituted himgaline (112), both installing the last nitrogen-containing ring (via an aza-Michael addition) giving oxohimgaline (not shown), and hydrogenating the resulting ketone to an alcohol (i.e.…”
Section: Chemical Degradationmentioning
confidence: 99%
“…[27] However, although this work provided substantial experience for the neovibsanins (see Schemes 3 and 4), it was not possible to convert the advanced intermediate into either of the targets. [116] Therefore, a more modern methodology was employed. However, it is always a concern when adopting new methods as many often fail when applied to complex systems.…”
Section: Formal Synthesismentioning
confidence: 99%
“…Chen and colleagues (16,21) showed increased autophagocytic markers in emphysema models, and autophagy-impaired mice have shown resistance to cigarette smoke-induced cilia shortening. Subsequent studies have suggested that DUOX1-dependent superoxide production may be regulated by autophagy proteins in airway epithelium (139). Histone deacetylase 6-mediated autophagy (78,81) and IFT gene expression (49) have also been linked to abnormal cilia structure.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…The Queensland group pursued a biogenetically modeled approach giving access to bicycle 8 ,17,18 which, although led to many advanced intermediates (i.e. 9 ), did not yield the target 19,20. The Davies group utilised three key cycloadditions to achieve a total synthesis of 5- epi -10- epi -vibsanin E 6 ; a rhodium-catalysed [4+3] and a subsequent heteronuclear [4+2] afforded bicycle 10 , followed by a photochemically induced [4+2] (Scheme 1).…”
mentioning
confidence: 99%
“…In the view that the Davies strategy readily provided multi-gram quantities of bicycle 10 11 and the Queensland group had significant end game experience with molecules of this type,19 including the development of a novel method utilising ylid 11 for introducing the enol ester side chain,20 it made sense to join forces in this common quest. In fact the initial fruits of this collaboration led to the first total synthesis of the natural product (−)-5- epi -vibsanin E ( 4 )9 in which many of the previous difficulties encountered with both introduction and stereocontrol of the side chains were overcome.…”
mentioning
confidence: 99%